LOGISTICS ISSUES IN THE PROCESS OF TRANSPORTATION OF CONSTRUCTION CARGO (Ustozlar uchun, 2026)
Transportation of construction cargo is one of the important stages of the construction process. This topic covers the methods of delivering construction materials (cement, brick, sand, gravel, reinforced concrete structures and other cargo) to the construction site, vehicles and the effective organization of the transportation process. It also discusses compliance with safety rules during cargo transportation, proper planning of logistics processes and methods for reducing transportation costs. The main goal of the topic is to analyze ways to effectively, quickly and safely carry out the process of transporting construction cargo.